2015
DOI: 10.3109/13880209.2014.997250
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory constituents fromPerovskia atriplicifolia

Abstract: Context: Perovskia atriplicifolia Benth (Labiantae) has long been used as a traditional herbal medicine for anti-inflammation in Pakistan; this prompted us to isolate anti-inflammatory compounds from this plant. Objective: The objective of this study was to isolate and characterize the anti-inflammatory principles from Perovskia atriplicifolia. Materials and methods: The CHCl 3 -soluble fraction of the methanol extract of the whole plant on column chromatography yielded compounds 1-6. The anti-inflammatory pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…Anti-inflammatory properties were also studied on several lignans isolated from chloroform extract of P. atriplicifolia leaves. [ 4 ] Taxiresinol was the most potent among six compounds and inhibited leukotriene C4 release from rat basophiles with IC 50 of 3.49 μM. However, in our study, we did not detect these lignans in the hydromethanolic extract, probably because chloroform is a better solvent for obtaining nonpolar compounds.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Anti-inflammatory properties were also studied on several lignans isolated from chloroform extract of P. atriplicifolia leaves. [ 4 ] Taxiresinol was the most potent among six compounds and inhibited leukotriene C4 release from rat basophiles with IC 50 of 3.49 μM. However, in our study, we did not detect these lignans in the hydromethanolic extract, probably because chloroform is a better solvent for obtaining nonpolar compounds.…”
Section: Discussioncontrasting
confidence: 67%
“…[ 1 2 3 ] Other compounds present in different parts of this plant include other phenolic acids, lignans, flavonoids, and di- and triterpenoids. [ 2 4 5 6 7 8 9 ] P. atriplicifolia is used as folk medicine to treat a variety of ailments, including diabetes. [ 10 11 12 ] However, the anecdotic information on the antidiabetic use of Perovskia sp.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported to possess antibacterial and anti‐inflammatory activities. [ ][ ] Some investigation on this plant has been conducted and many compounds has been isolated . Our previous investigation suggested that the petroleum ether extract of P .…”
Section: Introductionmentioning
confidence: 99%
“…SSG is a natural furofuran-type lignan with a glucose linked to the benzene ring. Its aglycone, syringaresinol, possesses diverse pharmacological activities including anti-hepatic fibrosis 7 , anticancer 8 , antithrombotic 13 , as well as ant-inflammatory 14 , cardiomyocytic protection 15 , and vascular relaxation 16 . Various mechanisms are involved in syringaresinol-mediated health benefits such as protection cells from damage 15 , stimulation cell cycle arrest 8 and enhancing nitric oxide (NO) production.…”
Section: Introductionmentioning
confidence: 99%